Measurement of optic nerve sheath diameter by ultrasound in healthy term neonates - Shih-Yun Lan; Hung-Lin Tai; Jainn-Jim Lin; Fan-Yun Lan; Hsin-Yu Tsai; Kuang-Lin Lin (Elsevier, 2021)
Background: Optic nerve sheath diameter (ONSD) ultrasound is a noninvasive and repeatable tool to dynamically evaluate intracranial pressure with high diagnostic accuracy; however, data in neonates are scarce. The aim of this study was to determine the reference value of ONSD and potential influencing factors in healthy term neonates. Methods: We retrospectively reviewed 250 full-term neonates who underwent cranial ultrasound as part of selective newborn screening over a 2-year period. Neonates with any of the following conditions were excluded: using mechanical ventilation, sedatives and/or vasopressors, or signs of infection which needed cerebrospinal fluid analysis and/or intracranial pathologies. Data on sex, gestational age, birth body weight, birth body height, birth head circumference, Apgar score and types of delivery were collected. The neurodevelopmental outcomes were reviewed. Results: A total of 234 neonates (123 girls and 111 boys) were included. The mean ONSD value was 3.30 ± 0.27 mm in the right eye and 3.30 ± 0.23 mm in the left eye, with no significant difference between both eyes (p = 0.797). Male neonates had a larger ONSD than female neonates (3.34 ± 0.22 mm versus 3.26 ± 0.20 mm, p = 0.007), and ONSD was correlated with birth weight in the males. Otherwise, there were no statistically significant associations between ONSD and other birth characteristics in both sexes. Most (63%) cases were followed for at least 12 months, and 98% had normal neurodevelopment. Conclusion: The reference value reported in this study may be used to evaluate the ONSD in healthy term neonates. Sex differences should be considered in this age group.